-d=-12

Simple and best practice solution for -d=-12 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -d=-12 equation:


Simplifying
-1d = -12

Solving
-1d = -12

Solving for variable 'd'.

Move all terms containing d to the left, all other terms to the right.

Divide each side by '-1'.
d = 12

Simplifying
d = 12

See similar equations:

| 9u^2+30u+25=0 | | s^2-6s-27= | | 19+(-39)+(-51)+25= | | 7-5x+10=47 | | s^2-8s+12= | | -35+(-89)= | | (-12x+30)+(-17x-4)=360-75-27 | | c^2+13c+42= | | 1/3x+3=-7/2x-3/2 | | 7-5(x-2)=47 | | 2+2(5)= | | 60(2)(1/2) | | 60(21/2) | | 1/3*-1/4 | | x^2+8xy-9y^2= | | 4x/4=10/4 | | -8+(-2)= | | 1/2x+1/3(-1/4y+10)=5 | | -3x+7x+(-2x)= | | 5x-3(-2x+4)=6 | | Log(x)=7.645 | | (4m-3)=15 | | ln(x)=7.645 | | [2p-3]=15 | | 46-2p=6-9p | | 5x+(-2x)+7= | | -6x-6(3x-2)=132 | | 46-2p=6-7p | | 2x-4/9=10 | | 31+x=0 | | (12x-4)+(14x-11)+(15x+5)=236 | | 6*12*9= |

Equations solver categories